The impact of surgeons’ experience and practice on postoperative cervical collar use after single-level anterior cervical discectomy and fusion: a cross-sectional survey in Heilongjiang province, China - Chang Liu; Kun Wang; Chenggang Jie; Xiaolin Yin; Yiting Zhou; Wei Zhao; Jiaxing Xu (BMC Musculoskeletal Disorders)
Abstract Purpose This study aimed to assess the preferences of spine surgeons in Heilongjiang Province regarding the duration of cervical collar use after single-level anterior cervical discectomy and fusion (ACDF) and to identify the factors influencing these preferences. Methods A cross-sectional survey was conducted in Heilongjiang Province from August 4 to August 11, 2024. A convenience sampling method was employed to survey 96 spine surgeons via an online questionnaire. Factors influencing the duration of cervical collar use were analysed via chi-square tests and binary logistic regression. Results Significant variation in the duration of cervical collar use was observed after single-level ACDF, with the shortest duration being no use (2.08%) and the longest being 12 weeks (4.17%). The most common duration was 3 weeks (65.63%). The factors influencing the duration of cervical collar use included the surgeon’s education level (χ²=10.902, P < 0.001), years of practice (χ²=12.565, P = 0.006), and annual case volume of single-level ACDF (χ²=9.438, P = 0.009). Notably, years of practice was identified as an independent factor influencing the duration of cervical collar use (OR = 0.572, 95% CI: 0.348~0.939; P = 0.027). Conclusions This survey shows that there are differences in the clinical practices of spine surgeons in Heilongjiang Province regarding the duration of cervical collar wearing after single-level ACDF. These research findings suggest the need to develop standardized guidelines and consensus, alongside improved postoperative health education, to reduce the related complications caused by the long-term use of cervical collars in patients, such as axial symptoms, and to improve patients’ quality of life after surgery.